Induction of Phase 2 Antioxidant Enzymes by Broccoli Sulforaphane: Perspectives in Maintaining the Antioxidant Activity of Vitamins A, C, and E - Boddupalli, Sekhar s.; Mein, Jonathan R.; James, Don R.; Lakkanna, Shantala (Frontiers in Genetics, 2012)
Consumption of fruits and vegetables is recognized as an important part of a healthy diet. Increased consumption of cruciferous vegetables in particular has been associated with a decreased risk of several degenerative and chronic diseases, including cardiovascular disease and certain cancers. Members of the cruciferous vegetable family, which includes broccoli, Brussels sprouts, cauliflower, and cabbage, accumulate significant concentrations of glucosinolates, which are metabolized in vivo to biologically active isothiocyanates (ITCs). The ITC sulforaphane, which is derived from glucoraphanin, has garnered particular interest due to its extraordinary ability to induce expression of several enzymes via the Keap1/Nrf2/ARE pathway. Nrf2/ARE gene products are typically characterized as Phase II detoxification enzymes and/or antioxidant (AO) enzymes. Over the last decade, human clinical studies have begun to provide in vivo evidence of both Phase II and AO enzyme induction by SF. Many AO enzymes are redox cycling enzymes that maintain redox homeostasis and activity of free radical scavengers such as such as vitamins A, C and E. In this review, we present the existing evidence for induction of PII and AO enzymes by SF, the interactions of SF-induced AO enzymes and proposed maintenance of the essential vitamins A, C and E, and, finally, the current view of genotypic effects on ITC metabolism and AO enzyme induction and function.